Riwayat penyakit infeksi dan kejadian stunting pada balita usia 24 – 60 bulan - Siti Horidah; Riski Dwi Prameswari; Noor Diah Erlinawati; Priyo Sasmito; Muntasir Muntasir (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: The problem of malnutrition, especially stunting in toddlers in Bandung City is quite high at 6.63%. The main cause of stunting is malnutrition. Lack of nutritional intake can be caused by a history of infectious diseases.Purpose: To determine the relationship between a history of infectious diseases and the incidence of stunting in toddlers aged 24-60 months.Method: This study used a Cross Sectional design. The population in this study was toddlers aged 24 months – 60 months. The study sample was 41 toddlers, taken using a simple random sampling technique. The inclusion criteria of the study sample were toddlers aged 24-60 months, living in the working area of the Cidadung Health Center. The instrument used is a questionnaire. Data analysis using chi-square test.Results: The small percentage of toddlers in this study who were stunted was 29.3%. There is a significant relationship between history of diarrhea and the incidence of stunting in toddlers (p = 0.037), and there is a significant relationship between history of ARI and the incidence of stunting in toddlers (p = 0.038).Conclusion: The incidence of stunting can be caused by a history of infectious diseases such as a history of diarrheal diseases and a history of ARI.Suggestion: It is recommended for health workers to be able to help provide health counseling, especially about the prevention of infectious diseases such as diarrhea and ARI.Keywords: Stunting; History of Diarrhea; History of ARI; Toddlers Pendahuluan: Masalah kekurangan gizi terutama stunting pada balita di Kota Bandung cukup tinggi yaitu 6,63%. Penyebab utama stunting adalah kekurangan gizi. Kekurangan asupan gizi dapat disebabkan oleh riwayat penyakit infeksi.Tujuan: Untuk mengetahui hubungan riwayat penyakit infeksi dengan kejadian stunting pada balita umur 24-60 bulan.Metode: Penelitian ini menggunakan desain Cross Sectional. Populasi pada penelitian ini adalah balita berumur 24–60 bulan, sampel penelitian sebanyak 41 balita, diambil menggunakan teknik simple random sampling. Kriteria Inklusi sampel penelitian adalah balita yang berumur 24-60 bulan, tinggal di wilayah kerja Puskesmas Cipadung. Instrumen yang digunakan adalah kuesioner. Analisis data menggunakan uji chi-square.Hasil: Pada penelitian ini balita yang mengalami stunting sebanyak 29.3%. Terdapat hubungan antara riwayat diare dengan kejadian stunting pada balita (p=0,037), dan juga terdapat hubungan antara riwayat ISPA dengan kejadian stunting pada balita (p=0,038).Simpulan: Kejadian stunting dapat disebabkan oleh adanya riwayat penyakit infeksi seperti riwayat penyakit diare dan riwayat penyakit ISPA.Saran: Disarankan kepada tenaga kesehatan agar dapat membatu memberikan penyuluhan kesehatan khususnya tentang pencegahan penyakit infeksi seperti diare dan ISPA.